T4 Pneumococcal Conjugate Vaccine Reduces Rate, Density And Duration Of Experimental Human Pneumococcal Colonisation: First Human Challenge Testing Of A Pneumococcal Vaccine. (10th November 2014) - Collins, AM; Wright, AD; Mitsi, E; Gritzfeld, JF; Hancock, C; Shaw, D; Pennington, SH; Morton, B; Ferreira, DM; Gordon, SB
Abstract : Objective: To determine the effect of the Pneumococcal Conjugate Vaccine (PCV-13) on experimental pneumococcal colonisation compared to Hepatitis A vaccination (control) in healthy participants. Design: Double blind randomised controlled trial. Setting: Clinical Research Unit in the Royal Liverpool University Hospital. Participants: 99 healthy participants aged 18–50 years were randomly assigned to receive PCV-13 (n = 49) or Hepatitis A (n = 50) vaccination according to a randomisation plan in blocks of ten. Interventions: Participants previously vaccinated with PCV or control were inoculated after 4 weeks with 80, 000C FU/100 µl pneumococcal bacteria (6B) 100 µl per naris. Participants were followed up for 21 days to determine pneumococcal colonisation by culture of nasal wash samples. Main outcome measures: The primary outcome measure was the culture of type 6B pneumococcus at either day 2, 7, 14 or 21 following inoculation. Secondary outcome measures included the density and duration of pneumococcal colonisation post inoculation of 6B and the presence of any other naturally acquired pneumococcal strains. Results: The PCV group showed a significantly reduced experimental colonisation rate 5/48 compared to the control group 23/48 (<0.001) [Figure 1 ]. Both the density and duration of colonisation were reduced in the PCV group compared to the control group following inoculation. The area under the density-time curve (total exposure) was significantly reduced in the PCV compared to control group (mean 8902 vs 267580 p = 0.0179). Conclusion: PCV reduces pneumococcal colonisation rate, density and duration in healthy adults. The Experimental Human Pneumococcal Colonisation (EHPC) model is a safe, effective and efficient method of analysing the efficacy of vaccination on pneumococcal colonisation. We suggest that this novel EHPC model can now be used as a platform for future pneumococcal vaccine testing, using small sample sizes and shorter time scales than community studies in order to reduce time and cost to market. We recommend that carriage rate, density and duration are all measured in these studies. Trial registration. EudraCT: 2012-005141-20. ISRCTN: 45340436.